MENYIKAPI AKTIVITAS BERJAMAAH DI MASJID SELAMA PANDEMI COVID-19: ANALISIS RESPON MASYARAKAT DALAM PERSPEKTIF TEOLOGIS - Muhammad Thohir; Nalindra Isnan Pangestu; Fiha Ainun Jariyah; Puga Sakti Wibowo (UIN Antasari Banjarmasin, 2021)
The habit of Muslims to pray in congregation in mosques has a great potential in transmitting the virus because many people gather in one place. There have been calls from the government and MUI as well as several mass organizations to regulate congregational activities at mosques. The public response in responding to this appeal certainly has significant implications in efforts to prevent the spread of the Covid-19 outbreak. This research aims to explain in a theological perspective about the public response in responding to congregational activities in mosques during the Covid-19 outbreak. The method used is a mixed method by distributing quantitative questionnaires and combining qualitative data. The results of the study revealed that at least the Muslims were divided into three groups, namely First, those who surrendered to their destiny, did not make dzahir efforts in dealing with this epidemic, so they remained in congregation in mosques without maintaining health protocols; Second, the Muslims who are too paranoid, use every effort to take precautions in a dzahir manner but are ignorant of spiritual matters; Third, the middle Muslims, namely those who are balanced, they remain in congregation but still follow health protocols. The attitude that should be applied is the third attitude by trying physically and mentally and ending with tawakal.